Fabrication and Characterization of Metal-Semiconductor-Metal n-GaN UV Photodetector by PA-MOCVD - Dadi Rusdiana; Sugianto Sugianto; Andi Suhandi; Sukirno Sukirno; Maman Budiman; Mohamad Barmawi (Jurnal Matematika & Sains, 2005)
Metal-semiconductor-metal ultraviolet photodetectors fabricated on GaN epitaxial layers grown on (0001) sapphire by plasma-assisted metal organic chemical vapor deposition (PA-MOCVD) method. The photodetector with a thin GaN layer of 0.7 Âµm exhibited a low dark current with a saturation value of 1.469 x 10-14 A. The responsivity was 0.56 A/W at a wavelength of 320 nm under a bias voltage of 2.5 V.